THE PROBLEM OF NATIONAL SELF-CONSCIOUSNESS FUTURE HIGHER SPECIALISTS PEDAGOGICAL INSTITUTION (Pedagogy of Higher and Secondary Education, 2001)
This article deals with the problem of forming students’ national consciousness in higher educational institutions. The author gives the data obtained as a result of verifying the experiments connected with the investigation of this problem.